CRISPR/Cas9-targeted mutagenesis of SlCMT4 causes changes in plant architecture and reproductive organs in tomato. Issue 1 (11th April 2022) - Guo, Xuhu; Zhao, Jianguo; Chen, Zhiwen; Qiao, Jun; Zhang, Yongfang; Shen, Hong; Hu, Zhongli
Abstract: DNA methylation participates widely in the regulation of gene expression in plants. To date, the regulation and function of DNA methylation is still unknown in tomato plants. Here, we generated SlCMT4 mutants using the CRISPR-Cas9 gene editing system. We observed severe developmental defects in CRISPR-Cas9-mediated SlCMT4 mutants, including small and thick leaves, increased lateral buds, defective stamens and pistils, small fruit size with reduced setting rate, and defective seed development. The alterations at hormonal levels (IAA, tZR, strigol) were consistent with the multibranching phenotype in SlCMT4 mutant plants. CRISPR-Cas9-mediated knockout of SlCMT4 induced the expression of two pollen-specific genes ( PMEI and PRALF ) that suppressed the development of pollen wall and pollen tube elongation, which is responsible for irregular and defective pollen. The small-sized fruit phenotype is probably associated with upregulated expression of the IMA gene and reduced seeds in the mutant lines. Furthermore, we performed whole-genome bisulfite sequencing (WGBS) of fruits and found that SlCMT4 knockout reduced genome-wide cytosine methylation. A reduction of methylation was also observed in a 2-kp region of the IMA and LOXB promoters in the SlCMT4 -mutant fruits, indicating that the hypermethylation status of the CHH context is critical for the inhibition of IMA and LOXB promoter activity. Our results show that SlCMT4 is required for normal development of tomato vegetative and reproductive organs. This study illuminates the function of SlCMT4 and sheds light on the molecular regulatory mechanism of tomato plant architecture and fruit development and ripening.